2013
DOI: 10.1186/2193-1801-2-154
|View full text |Cite
|
Sign up to set email alerts
|

Production and partial characterization of extracellular amylase enzyme from Bacillus amyloliquefaciens P-001

Abstract: Amylases are one of the most important enzymes in present-day biotechnology. The present study was concerned with the production and partial characterization of extracellular amylase from Bacillus amyloliquefaciens P-001. The effect of various fermentation conditions on amylase production through shake-flask culture was investigated. Enzyme production was induced by a variety of starchy substrate but corn flour was found to be a suitable natural source for maximum production. Tryptone and ammonium nitrate (0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 42 publications
11
77
2
3
Order By: Relevance
“…A decline in amylase activity afterwards was probably due to depletion of nutrients in the fermentation medium of the microorganisms, causing stressed and unfavourable conditions for the bacteria resulting in reduction of enzyme activity. Our reports were against the findings of Vijayalakshmi et al (2012) and Deb et al (2013), who demonstrated maximum amylase activity by Bacillus sp. at 48 h of incubation.…”
Section: Bacillus Mojavensis Strain Mn43contrasting
confidence: 38%
See 1 more Smart Citation
“…A decline in amylase activity afterwards was probably due to depletion of nutrients in the fermentation medium of the microorganisms, causing stressed and unfavourable conditions for the bacteria resulting in reduction of enzyme activity. Our reports were against the findings of Vijayalakshmi et al (2012) and Deb et al (2013), who demonstrated maximum amylase activity by Bacillus sp. at 48 h of incubation.…”
Section: Bacillus Mojavensis Strain Mn43contrasting
confidence: 38%
“…is an industrial important microorganism because of its rapid growth rate, secretion of enzyme into the extracellular medium and safe handling (Vijayalakshmi et al, 2012). Bacillus subtilis, Bacillus amyloliquefaciens and Bacillus licheniformis are used as bacterial workhorses in industrial microbial cultivations for the production of a variety of enzymes as well as fine biochemicals (Deb et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, invarious Bacillus spp. maximum amylase production was observed in pH range of 6.5 to 7.5 [33]. Earlier studies have revealed that fungi required slightly acidic pH and bacteria required neutral pH for optimum growth.…”
Section: Effect Of Different Naclconcentration On Amylase Activitymentioning
confidence: 78%
“…B. cereus strain isolated from Cuddalore harbour waters grew maximally in shake flask with highest Amylase activity at pH 8.0 which was sustained even at pH 11.0 (Annamalai et al, 2011). Deb et al 2013 obtained maximum amylase production after 48 hours of incubation in fermentation medium with initial pH 9.…”
Section: Optimization Of Ph and Growth Periodmentioning
confidence: 99%
“…The result showed that, in SSF among the three substrates tested addition of Wheat Bran as substrate showed highest enzyme production of 154.2±0.65 U/ml with specific activity of 0.29±0.01 U/mg ( Figure 3A). Deb et al, 2013 showed that the production of enzyme was highest when corn flour was used as carbon source. Whereas Singh et al, (2010) found that wheat bran as suitable source for improved amylase production.…”
Section: Production Of Amylase Using Agro Wastesmentioning
confidence: 99%